Effects of Subcapsularis Neuro Muscular Reduction (NMR) in Adhesive Capsulitis - Madiha Ali,Sehrish Ali,Abdul Ghafoor Sajjad,Syed Ali Hussain,Kinza Anwar, Mirza Sawaid Abbas , Madiha Ali, Sehrish Ali, Abdul Ghafoor Sajjad, Syed Ali Hussain, Kinza Anwar, Mirza Sawaid Abbas (Journal of Rawalpindi Medical College, 2019)
Background: To determine the effects of Subscapularis Neuromuscular Reduction (NMR) in Adhesive Capsulitis patients on pain, Range of Motion (ROM) and Quality of life. Methods: In this randomized controlled trail patients with freezing and frozen stage of Adhesive capsulitis and limited range of movement were included. Patients were randomly divided into control (Group A) and experimental group (Group B). The patients of Group A were treated with conventional physical therapy treatment protocol and patients of group B were treated with subscapularis neuromuscular reduction along with conventional physical therapy. The patient outcome measures were assessed using numeric pain rating scale (NPRS), SPADI (shoulder pain and disability index) and ranges via goniometry. Data was analyzed by SPSS 21. Results: Both group showed significant improvement, but the end value comparison showed significant difference. NMR (Neuromuscular Reduction) on Subscapularis muscles improved the pain, ROM and Patient functional status more as compared to the conventional physical therapy group. The NPRS mean value for control group was 2.90±1.09 and mean value for experimental group was 2.05±1.10with p value of 0.021 while the mean value of SPADI for control group was33.52±9.96 and for experimental group was 26.72±8.00 with p value of 0.026. Conclusion: Treatment groups showed improvement by reducing pain, improving range of motion and functional status but neuromuscular reduction of subscapularis muscles was found to be more effective.